2020
DOI: 10.1111/hae.14105
|View full text |Cite
|
Sign up to set email alerts
|

Non‐severe haemophilia: Is it benign? – Insights from the PROBE study

Abstract: Introduction There are limited data on the impact of haemophilia on health status and health‐related quality of life (HRQL) in people with non‐severe (mild and moderate) haemophilia. Aim To evaluate the health status of people living with mild or moderate haemophilia. Methods Data on respondents with no bleeding disorder (NoBD), mild and moderate haemophilia patients were drawn from the PROBE study. Respondents were enrolled using network patient organizations. This analysis was performed as a cross‐sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 12 publications
5
37
0
Order By: Relevance
“…The experts convened were not intended to provide global expertise. However, some of the data presented in this supplement are global in nature, 15 and these data could inform other countries to apply the findings locally and make assessments. In addition, although the roundtable was a structured meeting, the discussions on which this paper is based report on the aggregate reflections of the group; a formal process for the adoption of a consensus was not employed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The experts convened were not intended to provide global expertise. However, some of the data presented in this supplement are global in nature, 15 and these data could inform other countries to apply the findings locally and make assessments. In addition, although the roundtable was a structured meeting, the discussions on which this paper is based report on the aggregate reflections of the group; a formal process for the adoption of a consensus was not employed.…”
Section: Discussionmentioning
confidence: 99%
“…During a roundtable meeting, participants were tasked with defining the unmet needs of this population and developing potential solutions following a discussion of pertinent data and findings (some unpublished), including the Pain, Functional Impairment, and Quality of Life (P‐FiQ), 9,10 the Bridging Hemophilia B Experiences, Results and Opportunities Into Solutions (B‐HERO‐S), 10‐14 the Community Having Opportunity to Influence Care Equity (CHOICE) (unpublished data), and the Patient Reported Outcomes, Burdens, and Experiences (PROBE) 15 studies. Select data from these studies are presented in this supplement 10,15 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study identified issues with pain, joint range of motion and activities of daily living. Importantly, problems with access to treatment for women were also found 21 …”
Section: Addressing Unmet Needs In Mild‐to‐moderate Haemophiliamentioning
confidence: 99%